South Asia Bible commentary - Wintle Brian; Wintle, Brian C. (Brian Charles), 1944- (Rajasthan, India : Open Door Publications ; Cumbria, UK : Langham Partnership ; Grand Rapids, Michigan : Zondervan, 2015)
"A one-volume commentary, written and edited by South Asian Biblical scholars on all the books of the Bible"--
Includes bibliographical references.
Keywords: Bible -- Commentaries; South Asia Bible Commentary: A one-volume commentary on the whole Bible -- South Asia; Commentaries